Efektivitas penggunaan video pembelajaran terhadap hasil belajar konsep dasar perkalian di kelas III fase B - Aziz Ayi Nugraha; Karlimah; Muhammad Rijal Wahid Muharram (COLLASE (Creative of Learning Students Elementary Education), 2026)
Abstract Mathematics as an important subject in elementary school is often challenging for students, especially in understanding the basic concept of multiplication. This study aims to test the effectiveness of learning videos as an innovative media in improving student learning outcomes in multiplication material. The research method used is an experiment with a nonequivalent control group design. The subjects of the study involved third-grade students in two elementary schools, who were divided into experimental and control groups. Data were obtained through pretests and posttests to evaluate students' abilities before and after using learning videos. The results showed that the use of learning videos significantly improved students' understanding of the concept of multiplication compared to conventional lecture methods. Students in the experimental group showed a higher increase in learning outcomes based on the calculation of the gain index. These findings confirm that learning videos are effective in visualizing abstract concepts, creating an interactive learning atmosphere, and increasing students' learning motivation. This study concludes that the integration of video media in mathematics learning can be an innovative solution to improve student learning outcomes at the elementary level. Keywords : learning videos, learning outcomes, multiplication. Abstrak Matematika sebagai mata pelajaran penting di sekolah dasar sering kali menantang bagi siswa, khususnya dalam memahami konsep dasar perkalian. Penelitian ini bertujuan untuk menguji efektivitas video pembelajaran sebagai media inovatif dalam meningkatkan hasil belajar siswa pada materi perkalian. Metode penelitian yang digunakan adalah eksperimen dengan desain nonequivalent control group. Subjek penelitian melibatkan siswa kelas III di dua sekolah dasar, yang dibagi ke dalam kelompok eksperimen dan kontrol. Data diperoleh melalui pretest dan posttest untuk mengevaluasi kemampuan siswa sebelum dan sesudah menggunakan video pembelajaran. Hasil penelitian menunjukkan bahwa penggunaan video pembelajaran secara signifikan meningkatkan pemahaman siswa terhadap konsep perkalian dibandingkan dengan metode ceramah konvensional. Siswa dalam kelompok eksperimen menunjukkan peningkatan hasil belajar yang lebih tinggi berdasarkan perhitungan indeks gain. Temuan ini menegaskan bahwa video pembelajaran efektif dalam memvisualisasikan konsep abstrak, menciptakan suasana belajar yang interaktif, dan meningkatkan motivasi belajar siswa. Penelitian ini menyimpulkan bahwa integrasi media video dalam pembelajaran matematika dapat menjadi solusi inovatif untuk memperbaiki hasil belajar siswa di tingkat dasar. Kata Kunci: video pembelajaran, hasil belajar, perkalian.